On Editing Luther's Writings on Scripture. Issue 2 (June 2017) - Cameron, Euan K.
Abstract: Much of Martin Luther's prodigious output consisted of exposition and editing Scripture. While a series in English cannot do justice to his greatest achievement, his Bible in German, much can be learned from his prefaces and commentaries, which are selected in volume 6 of The Annotated Luther . Luther's attitude to interpreting Scripture evolved in a constant dialogue with his theology of justification. While he held to the absolute authority of Scripture, his approach was pre‐critical but not uncritical. His exposition constantly balanced the consolation of grace and warnings against complacent trusting in our own works. His relentless emphasis on seeing Christ everywhere in the Bible, praised in past generations, poses problems today insofar as it determined his stance against Judaism.